Energy management system in buildings - Oo, Nay (2016)
Today, the power grid has evolved to facilitate complex needs of consumers and to help utilities service providers meet the electricity and energy requirement without spending and wasting more resources than what is necessary. It is important to support the power grid with latest advancements such as smart sensors, communication devices and building energy management system (BEMS). This project aims to complete a full-fledged BEMS which is an essential part of the smart power grid. The system is expected to have enough capabilities to maintain the building’s total power demand lower than the value specified by the building owner and property managers. Moreover, the system is capable of providing real time power usage information. The BEMS completed for this project has all the basic requirements of a smart building such as renewable energy source, battery system to support demand side management, typical loads installed in modern buildings, etc. It also employs an effective and practical demand response algorithm which maintain the maximum demand of the building in order to save energy cost for the owner. It is also equipped with necessary computing and smart communication devices to monitor and control all the electrical loads in the buildings. The final BEMS can also be used as a testing platform for exploring new demand side management protocols and algorithms. Different energy management techniques such as priority based load-shedding, load shifting, and energy efficiency methods are employed in this BEMS. The software and algorithm required are graphically programmed using LabVIEW which supports simple implementation of complex system during the development stage of the project.